Acting on iniquities. The aboriginal everyday struggle for health. An anthropological case study among the atikamekw on-reserve community of manawan - Québec, Canada - Mendes, Felismina (2012)
In Canada, Aboriginal people represent a minority in some measure excluded by the high socio-economical levels and health standard of the country. Through an ethnographical study he conducted among the Atikamekw reserve of Manawan – Qc, the author of this work explores and investigates the conditions of possibility for an Aboriginal on-reserve community, to locally act in the direction of a transformative change on the pathogenic system affecting their health. And he eventually opens a glimmer on the much at stake concerning the health of Aboriginal people.